2021
DOI: 10.1177/1097184x211038049
|View full text |Cite
|
Sign up to set email alerts
|

From Military Masculinity toward Hybrid Masculinities: Constructing a New Sense of Manhood among Veterans Treated for PTSS

Abstract: This study examines how Israeli men who are army veterans with combat-related post-traumatic stress and consequently participated in therapy engage “new masculinities” ideologies. Drawing from interview data with these veterans, we find changes in the men’s perceptions of masculinity and sense of themselves as men. They expressed this shift through criticisms of military masculinity and disassociating from the idea of man-as-fighter, disputing the sociocultural category of hegemonic masculinity, and performing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…In sum, our findings indicated that higher endorsement of self-reliance may impede the effects of treatment on outcome; however, toughness endorsement was associated with greater improvement in psychosocial functioning after treatment was over. These findings are consistent with the argument that different aspects of traditional masculinity norms have differing impacts on treatment outcome among men (e.g., Spector-Mersel & Gilbar, 2021).…”
Section: Resultssupporting
confidence: 89%
“…In sum, our findings indicated that higher endorsement of self-reliance may impede the effects of treatment on outcome; however, toughness endorsement was associated with greater improvement in psychosocial functioning after treatment was over. These findings are consistent with the argument that different aspects of traditional masculinity norms have differing impacts on treatment outcome among men (e.g., Spector-Mersel & Gilbar, 2021).…”
Section: Resultssupporting
confidence: 89%
“…There is a particular need to screen and assess men’s perception regarding failure to comply with hegemonic gender norms, since this failure may intensify the risk of harming themselves by disengaging from services or of bidirectional IPV. Second, programs are advised to encourage reformulation of masculinity by deconstructing gender binaries regarding who can engage in particular expressions of gender and highlighting the inherent limits of traditional masculinity, such as avoidance of sharing emotions, which could enhance their help-seeking behavior and recovery (Spector-Mersel & Gilbar, 2021). In line with these approaches and the therapeutic value of cross-gender experience of victimization found here, the promotion of cross-gender struggle against violence is recommended.…”
Section: Clinical and Policy Implicationsmentioning
confidence: 99%
“…How can we create interventions that consider a revised military masculine culture within which distress occurs? A shift toward inclusivity, mutual support, and collaboration would embody a person-centered approach, often deemphasized in medicalized approaches (Callaghan, 2014;Cocker & Joss, 2016;Laska et al, 2013;Resick et al, 2015;Spector-Mersel & Gilbar, 2021). Collaboration extends beyond patient-provider relationships.…”
Section: Implications: the Social Ecology Of Military/veteran Ptsdmentioning
confidence: 99%